Influence of exercise order on repetition performance among all possible combinations on resistance training - Miranda, H.; Figueiredo, T.; Rodrigues, B.; Andrade Paz, G.; Simao, R. (Research in Sports Medicine, 2013)
The purposes of this study were to compare the repetition performance and rating of perceived exertion (RPE) in different exercises order of three resistance training (RT) exercises: bench press (BP), shoulder press (SP), and triceps extension (TE). Twelve trained men participated in this study (26.75 ± 2.49 years; 177 ± 4.66 cm; 77.7 ± 6.20 kg; 12.61 ± 2.01% body fat; RT experience 3.58 ± 1.24 years). Data were collected in two phases: (1) 10 RM test for BP, SP, and TE and (2) performance of six RT sequences. The sequences were: SEQA (BP, SP, TE), SEQB (BP, TE, SP), SEQC (SP, BP, TE), SEQD (SP, TE, BP), SEQE (TE, BP, SP), and SEQF (TE, SP, BP). The repetition performance on SEQD was significantly smaller than SEQE and SEQF. No significant differences were found for repetition performance and RPE among other sequences. These data indicate that priority might be given to exercises performed in the beginning of the RT session.